Formation at students of volontersky professional skills. (The Journal of Psychology and Sociology, 2012)
The statement of civil, humanistic values in society, education of the free personality realizing interdependence of the rights and duties in many respects depends on a younger generation education system that is deﬁ ned by preparation of the teacher, the head and the organizer of educational process in higher education institution. One of the most perspective tendencies of professional pedagogical education is formation of volontyorsky professional competence of future expert which assumes transition from a rigid regulation of educational process in higher education institution to the humanistic educational space based on a voluntary choice of forms of activity, trust to the young people, focused on a harmonious combination of universal values.
Keywords: civil society; young people; universal value; professional competence.